2018
DOI: 10.18052/www.scipress.com/ijppe.10.1
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activity and Antioxidants of <i>Hydrocotyle vulgaris </i>L<i>.</i> (Pennywort): Baseline Study in Developing Biocosmetic-Antidote for Pathological Aging

Abstract: Abstract. Pathological aging due to harmful free radicals and oxidative stress has been a serious threat to human health. Thus, the study aimed to evaluate the free radical scavenging activity, antioxidants, essential vitamins, and physicochemical properties of Hydrocotyle vulgaris L. (Pennywort) which could serve as basis in developing a biocosmetic antidote for pathological aging. H. vulgaris L. plant was harvested, air dried and then extracted via soxhlet. UV-vis spectroscopy was used for scavenging activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Based on the results, the IC50 of apple cider solution, vinegar, dodol, chip, apple fruit, and vitamin C is 3,691,278.89 ppm; 2,224,333.33 ppm; 123,939.94 ppm, 13,871.63 ppm; 36,722.36 ppm, and 96.71 ppm, respectively. A smaller IC50 value means that the activity of the test solution is more effective as an antidote to free radicals (Ureta et al, 2018). The results of statistical tests using ANOVA SPSS 19 to compare the IC50 results from apple cider, apple vinegar, apple dodol, apple chips, and manalagi apple found that the value of P-value (0,000) ≤ 0.05, therefore there was a significant difference in IC50 value among the test solutions.…”
Section: Engrid Et Al | the Antioxidant Activity … 49mentioning
confidence: 99%
“…Based on the results, the IC50 of apple cider solution, vinegar, dodol, chip, apple fruit, and vitamin C is 3,691,278.89 ppm; 2,224,333.33 ppm; 123,939.94 ppm, 13,871.63 ppm; 36,722.36 ppm, and 96.71 ppm, respectively. A smaller IC50 value means that the activity of the test solution is more effective as an antidote to free radicals (Ureta et al, 2018). The results of statistical tests using ANOVA SPSS 19 to compare the IC50 results from apple cider, apple vinegar, apple dodol, apple chips, and manalagi apple found that the value of P-value (0,000) ≤ 0.05, therefore there was a significant difference in IC50 value among the test solutions.…”
Section: Engrid Et Al | the Antioxidant Activity … 49mentioning
confidence: 99%